Determining the causality indices of controlled dynamic systems; Soviet journal of computer and systems sciences; Vol. 28, Issue 4 - Malishenko (Malyshenko) A. M. Alexanedr Maximovich (1990, 1990)
The notion of causality indices for controlled multidimensional continuous- and discrete-time dynamic systems is introduced. Methods for their determination from the system digraph The procedure for calculating the causality indices by reference to the system digraph can be replaced by computing these indices from the reachability matrices that correspond to it, which are formed from the adjacency matrix of the digraph An example is given for a linear system